Aqueous binder effects of poly(acrylic acid) and carboxy methylated cellulose on anode performance in lithium-ion batteries. (17th July 2019) - Yang, Xiaofei; Zhang, Huimin; Ming, Hai; Qiu, Jingyi; Cao, Gaoping; Li, Meng; Zhu, Xiayu; Sui, Chen; Zhang, Tingting; Ming, Jun
Abstract : The aqueous binder effects of poly(acrylic acid) and carboxy methylated cellulose on metal (oxide) anode performance in lithium-ion batteries were studied. Abstract : The binder effect of poly(acrylic acid) (PAA) and carboxy methylated cellulose (CMC) is investigated based on a metal oxide anode ( e.g., Co3 O4 ), which was prepared from metal nitrate decomposition without further engineering on the nanostructures and carbon modification. We find that the combined binder of PAA and CMC has a good coupling contribution to the electrochemical performance. Distinct from the traditional approaches pursuing advanced structures and/or carbon modification, the presented strategy herein is more convenient, environment-friendly and available for industrial production. For example, the model of Co3 O4 can exhibit an extremely high capacity of 700 mA h g −1 at the current density of 200 mA g −1 and a reversible capacity over 620 mA h g −1 beyond 150 cycles. In addition, a model of full batteries employing a pre-lithiated Co3 O4 anode versus a LiNi1/3 Co1/3 Mn1/3 O2 @AlPO4 cathode with a higher energy density is studied, demonstrating the availability of the presented PAA/CMC binder towards commercialization. Thus, we conclude that the combined aqueous binder of PAA/CMC can have a positive effect on the electrochemical performance of the metal oxide anodes in lithium (ion) batteries, which may be extended further to other advanced metal-ion (Na +, Mg 2+, Al 3+, etc. ) batteries.